Covid19 in pregnancy—a literature review - Shazia Saaqib; Yasaan Saaqib; Minha Zeeshan (Journal of the Pakistan Medical Association, 2022)
Coronavirus disease-2019, or Covid-19, was first reported in Wuhan, China, at the end of December 2019 as viral pneumonia. The causative agent, the Novel Coronavirus severe acute respiratory syndrome (SARS) CoV-2, spread rapidly across the world to cause a considerable death toll. On March 11, 2020, the World Health Organisation declared Covid-19 a pandemic. For a little over a year, the coronavirus has been around. Pregnancy is an immunodeficient state predisposing women to an increased risk of respiratory viral infections. The risk is even higher in pregnant women who already have underlying health problems due to growing age, such as diabetes, hypertension, cardiac or respiratory diseases. The exact treatment of Covid-19 is still unknown. This narrative review was planned to summarise the current information on pathophysiology, diagnosis and effects of Covid-19 in pregnancy for better treatment plans. Key Words: Coronavirus, Pneumonia, Pandemic, Pregnant women. Continuous...